Follistatin-like 1 (FSTL1) is a prognostic biomarker and correlated with immune cell infiltration in gastric cancer - Li, Li (World J Surg Oncol, 2020)
BACKGROUND: Follistatin-like 1 (FSTL1) plays a central role in the progression of tumor and tumor immunity. However, the effect of FSTL1 on the prognosis and immune infiltration of gastric cancer (GC) remains to be elucidated. METHODS: The expression of FSTL1 data was analyzed in Oncomine and TIMER databases. Analyses of clinical parameters and survival data were conducted by Kaplan-Meier plotter and immunohistochemistry. Western blot assay and real-time quantitative PCR (RT-qPCR) were used to analyze protein and mRNA expression, respectively. The correlations between FSTL1 and cancer immune infiltrates were analyzed by Tumor Immune Estimation Resource (TIME), Gene Expression Profiling Interactive Analysis (GEPIA), and LinkedOmics database. RESULTS: The expression of FSTL1 was significantly higher in GC tissues than in normal tissues, and bioinformatic analysis and immunohistochemistry (IHC) indicated that high FSTL1 expression significantly correlated with poor prognosis in GC. Moreover, FSTL1 was predicted as an independent prognostic factor in GC patients. Bioinformatics analysis results suggested that FSTL1 mainly involved in tumor progression and tumor immunity. And significant correlations were found between FSTL1 expression and immune cell infiltration in GC. CONCLUSIONS: The study effectively revealed useful information about FSTL1 expression, prognostic values, potential functional networks, and impact of tumor immune infiltration in GC. In summary, FSTL1 can be used as a biomarker for prognosis and evaluating immune cell infiltration in GC. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12957-020-02070-9.